The Challenge of Local Revenue Enhancement through Boarding House Taxation Policy in Yogyakarta City - Fatimah Nuraini; Nasrullah Nasrullah; Abd Hamid Bin Abd Murad (Jurnal Hukum Novelty, 2022)
Introduction to The Problem: In early 2019, the total data on Building Permits for Boarding Houses in Yogyakarta City reached more than 700 houses, and the local tax revenue for the category Boarding House did not reach 40 homes yearly. The urgency of enforcement of the boarding house tax regulation is relevant to increasing tax compliance rates and local revenue from boarding houses.Objective Study: This study examines the enforcement of the Regional Regulation of Number 1 of 2011 on Local Tax and the obstacles to its implementation using the law system components, the law enforcement factors and the law enforcement elements.Methodology: The data used are primary data and secondary data through a regulatory approach. Data collection uses a structured interview process by interviewing five interviewees who handled the enforcement of boarding house tax rules.Findings: The service quality of tax authority factor, law enforcement officers’ factor, and tax sanctions factor have adjusted the public needs (as a legal benefit) and legal certainty while does not provide justice to the community. Implications of the study for tax policy of the Boarding House category are the imposition of criminal sanctions and administrative sanctions against non-compliance boarding house taxpayers, the coordination between tax authorities and law enforcers to enforce boarding house tax rules, and the development of boarding house tax regulations relating to the tax sanctions theory.Paper Type: Research Article